Penafsiran Ayat-Ayat Jihad dan Khilafah: Upaya Menanggulangi Paham Ekstremisme di UNIDA Gontor - Ali Mahfuz Munawar; A Fadly Rahman Akbar; Muttaqin (Universitas Darussalam Gontor, 2021)
Jihad to establish a Khilāfah state has again become a viral issue studied and discussed by scholars, academics, politicians and activists. Consequently, there is a tendency to consider the political system as one of the pillars of religion. The tendency to consider the Khilāfah as a legitimate form of government and guarantee the application of sharia law post the Prophet period. This is a trend that has never been known by religion and ijtihad of previous Muslims even almost causing division and destruction in many countries. This article is aimed to analyze the interpretation of verse of jihad and khilafah in university students’ point of view. It was because that students in universities have an important and strategic role in warding off the dangers of radicalism and intolerance that develop in society. Students are expected to be the important pillar to reduce the development of radicalism. University of Darussalam Gontor (UNIDA Gontor) as a boarding school with the motto of the fountain of wisdom, is expected to be able to overcome radicalism and extremism in terms of khilāfah and jihad. This study used quaitative method to gain the data.This study revealed that UNIDA Gontor students had understood the meaning of khilafah and jihad properly and correctly only some deficiencies such as references.it was not only about tolerant or in accordance with the manhaj ahlu sunnah wal jama'ah and moderate washatiyah mazhab. It stated that the khilāfah is impossible to stand again, and the need for correct references in understanding the khilāfah and jihad.